THU0431 Are extremity telangiectases related to severe disease in systemic sclerosis ?. (12th June 2018) - Yalçınkaya, Y.; Pehlivan, O.; Ertürk, Z.; Gazel, U.; Aksoy, A.; Alibaz-Oner, F.; Atagunduz, P.; Direskeneli, H.; Inanc, N.
Abstract : Background: The number and morphology of telangiectases (T) have been studied in terms of severity and organ involvement in sytemic sclerosis (SSc). T are located more frequently on face and trunk than extremities. Objectives: We aimed to evaluate the impact of the localisation of T on different skin areas in addition to number on disease severity of SSc. Methods: SSc patients fulfilling ACR/EULAR classification criteria (2013) who had the manifestation T were included. The number of T were calculated by using telangiectasia score (TS) (Shah A., et al) and localisation was classified according to presence of T on extremities or not. Simultaneously; ealy, active and late scleroderma patterns (Cutolo et al.) were determined qualitatively and capillary number (CN) was calculated per linear mm at distal row quantitatively by using nail fold video-capillaroscopy (NVC) in all patients. Results: In 113 (106 female) SSc patients with T; the mean age was 52±12, the duration of follow-up 57±62 months, Raynaud and non-Raynaud symptom 10±8 and 7±7 years. Limited cutaneous form was found to be in 77 (%68), ANA positivity in 102 (%90) ve anti-Scl70 positivity in 33 (%29) patients. In SSc patients with TS score ≥6 or extremity T; the duration of non-Raynaud symptom was found to be longer (p=0010 or 0, 009), MRSS and activity scores were higher (p=0004 or 0012 and p=0010 or 0, 009) and severity scores of general, peripheral vascular involvement and skin were higher (p=0022 or 0, 014, p=0030 or 0025 and p=0006 or 0, 02), digital ulcers and flexion contractures were more frequent (p=0008 or 0035 and p=0027 or 0, 032), late NVC pattern was more frequent and CN was lower (p=0001 or 0003 and p=0001 or 0, 007). When patients were classified in 3 groups according to TS and presence of extremity T, differences in terms of organ involvement, disease activity and severity scores and NVC findings were summarised in table 1. Conclusions: Disease duration was shown to be long, disease activity and severity were high and NVC findings were severe in patients with high scores of TS and extremity T. In patients with lower TS the presence of T on extremities was found to be related to severe disease. The number and localisation of T was emphasised as they are easy to evaluate in clinical practice and may be useful in determining severe patients with SSc. Disclosure of Interest: None declared